Development of the Health Service System for HIV/AIDS Patients in Northeastern Community Hospitals(Thai) - Boonyalccpun, Suwanna; Laohasiriwong, Wongsa; Saengsuwan, Jiamjit; Sanchaisuriya, Pattara; Kasalaraksa, Pobe; Rittirod, Theera; Siripakarn, Ploenta; Duangdee, Aree; Loaprasert, Prakaytip; Pramintara, Surachana; Bounma, Sudawadee; Saimonka, Wanpen (Asia-Pacific Journal of Science and Technology, 2017)
This action research aimed to develop the health service system for HIV/ AIDS patients in hospitals. The research was conducted in 2 community hospitals during July 2003 to March 2004. The participants were 20 health personnel, 41 people living with HIV/AIDS (PHAs), and 30 caregivers. The research process included collecting both qualitative and quantitative data by in-depth interview, focus group discussions and non-participatory observations for problem identification. Alt stakeholders were involved in planning for intervention through several meetings. The appropriateness and continuity of the HIV/ AIDS health care service system was developed participatory and implemented by all sectors, Data were analyzed by content analysis. The development process for appropriateness and continuity of care for PHAs in the hospital had 2 phases. The immediate development phase included: 1) training workshop on counseling and techniques in caring for patients with antiretroviral therapy (ART), 2) study visit to community hospital which is well established in HIV/ AIDS health care service. This study visit aimed to make health personnel, PHAs and care givers have a clear picture of appropriateness and continuity of HIV/ AIDS health care service system. The long term development phases of the appropriateness and continuity of an HIV/ AIDS health care service system were development of HIV/ AIDS health care system, practice guidelines, and caring standards for HIV/ AIDS patients, Both hospitals established a center responsible for HIV/ AIDS patient data and information. The caring system has been developed to cover these 4 aspects which needs administrator support in terms of policy and resources.